Vitamin D–Related Genetic Variation, Plasma Vitamin D, and Risk of Lethal Prostate Cancer: A Prospective Nested Case–Control Study - Shui, Irene M.; Mucci, Lorelei A.; Kraft, Peter; Tamimi, Rulla M.; Lindstrom, Sara; Penney, Kathryn L.; Nimptsch, Katharina; Hollis, Bruce W.; DuPre, Natalie; Platz, Elizabeth A.; Stampfer, Meir J.; Giovannucci, Edward (JNCI : Journal of the National Cancer Institute, 2012)
The association of vitamin D status with prostate cancer is controversial; no association has been observed for overall incidence, but there is a potential link with lethal disease. We assessed prediagnostic 25-hydroxyvitamin D [25(OH)D] levels in plasma, variation in vitamin D-related genes, and risk of lethal prostate cancer using a prospective case-control study nested within the Health Professionals Follow-up Study. We included 1260 men who were diagnosed with prostate cancer after providing a blood sample in 1993-1995 and 1331 control subjects. Men with prostate cancer were followed through March 2011 for lethal outcomes (n = 114). We selected 97 single-nucleotide polymorphisms (SNPs) in genomic regions with high linkage disequilibrium (tagSNPs) to represent common genetic variation among seven vitamin D-related genes (CYP27A1, CYP2R1, CYP27B1, GC, CYP24A1, RXRA, and VDR). We used a logistic kernel machine test to assess whether multimarker SNP sets in seven vitamin D pathway-related genes were collectively associated with prostate cancer. Tests for statistical significance were two-sided. Higher 25(OH)D levels were associated with a 57% reduction in the risk of lethal prostate cancer (highest vs lowest quartile: odds ratio = 0.43, 95% confidence interval = 0.24 to 0.76). This finding did not vary by time from blood collection to diagnosis. We found no statistically significant association of plasma 25(OH)D levels with overall prostate cancer. Pathway analyses found that the set of SNPs that included all seven genes (P = .008) as well as sets of SNPs that included VDR (P = .01) and CYP27A1 (P = .02) were associated with risk of lethal prostate cancer. In this prospective study, plasma 25(OH)D levels and common variation among several vitamin D-related genes were associated with lethal prostate cancer risk, suggesting that vitamin D is relevant for lethal prostate cancer.